Midwifery Students, Perspectives about Their Motivation for Choosing Midwifery as a Career - K. Arfaei; Z. Soofi-Abadi (Iran University of Medical Sciences, 2010)
Background and Aim: Motivation is an internal feeling that provokes, sterenghtens and finally leads behaviors. For activities such as learning, there are various incentives drives. The aim of the present study was to identify the motivational factors in choosing midwifery as a career form perspectives of midwifery students studying at Semnan Azad University, Iran, in 2010.   Materials and Method: This descriptive study was conducted with a sample of of 120 midwifery students of Semnan Azad University. The subjects were selected by census sampling method. Data were collected by a questionaire whose validity and reliability were provided. Data were analyzed by SPSS program.   Results: "Career interest" and "having a career with suitable spare times" were, respectively, the most and the least important motivational factors in choosing midwifery as a career. "Social perestige" and "job opurtunities" were not important motivational factors in choosing the midwifery career.   Conclusion: It can be concluded that only personal motivation, morality and the nature of the occupation is important in choosing midwifery career and ideal social status and meeting life standards do not have any impotance. Authorities should search for solving occupational problems and shed light to real position of the proffesoin to provide more job openings for the youth.